Effects of Coadministration of Vitamin C and Lamotrigine on some Pharmacological Properties of Lamotrigine in Laboratory Animals - Yusuf, Muhammad Shamsuddeen; Malami, Sani; Danjuma, Nuhu Muhammad; Salisu, Hadiza Mai’adua; Dogara, Jibril Kabir; Bako, Nuhu Aliyu; Kabiru, Abdulkadir Muhammad (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Despite the continued development and release of new antiepileptic drugs, many patients have seizures that do not respond to drug therapy or have related side effects that preclude continued use. The present study is aimed at establishing the possible potentiation actions of vitamin C on the anticonvulsant effects of lamotrigine in acute and chronic seizure models and on the possible prevention and/or reversal of haematological side effects of lamotrigine. This aim was achieved using maximal electroshock test (MEST)-induced seizure model for which the method of Swinyard and Kupferberg, (1985) was adopted, pentylenetetrazole-induced kindling model for which method described by Gupta et al., (2001) was employed and haematological analysis in which haemoglobin concentration, packed cell volume, red blood cell count, white blood cell count / differentials and platelets count were carried out. Lamotrigine and Vitamin C combination at doses of 50 mg/kg, 100 mg/kg and 400 mg/kg provided 16.67%, 50%, and 66.67% protection respectively against MEST-induced seizures. There was no significant (p < 0.05) difference in the mean recovery period. Lamotrigine only showed 0% protection against MEST-induced seizures. In PTZ induced kindling, Vitamin C (50 mg/kg and 400 mg/kg) showed a significant (p < 0.05) reduction (from 5.00 to 0.88 and 5.00 to 2.13 respectively) in the severity of seizure induced by sub-convulsive dose (35 mg/kg) of PTZ as compared to control group on day ten. Administration of lamotrigine caused a reduction in mean neutrophils count as against untreated control group. Addition of vitamin C (50 mg/kg and 100 mg/kg) to lamotrigine treated group caused an increase in neutrophils compared to lamotrigine only treated group. The results showed that vitamin C enhances the anticonvulsant and some haematological sideeffects of lamotrigine, thus may serve as an adjunct in treatment of epilepsy using lamotrigine.